Demo: ThingsMigrate - Platform-Independent Live-Migration of JavaScript Processes - Jung, Kumseok; Gascon-Samson, Julien; Pattabiraman, Karthik (2018 IEEE ACM Symposium on Edge Computing (SEC), 2018)
Recent trends in IoT (Internet of Things) has seen increasing number of devices being shipped with full-fledged operating systems, allowing more complex and stateful applications written in high-level languages (e.g., JavaScript) to be run on the edge. The benefits of pushing computations towards the edge is that one can reduce the network costs of data transmission. Just like any other distributed system, we need to guarantee in IoT the availability of running processes, and thus need a live-migration mechanism for such programs. However, well-studied VM migration techniques are costly and impractical in IoT, due to the resource constraints and diversity of devices. In this demo paper, we present a demo of ThingsMigrate, a JavaScript middleware for enabling live-migration of stateful JavaScript applications in a platform-independent manner, along with a web dashboard used to monitor and control the IoT devices.